2022
DOI: 10.1002/jcc.26981
|View full text |Cite
|
Sign up to set email alerts
|

Investigation of glucose electrooxidation mechanism over N‐modified metal‐doped graphene electrode by density functional theory approach

Abstract: In this work, various precious and non‐precious metals reported in the literature as the most effective catalysts for glucose electrooxidation reaction were investigated by the density functional theory (DFT) approach in order to reveal the mechanisms taking place over the catalysts in the fuel cell. The use of a single‐atom catalyst model was adopted by insertion of one Au, Cu, Ni, Pd, Pt, and Zn metal atom on the pyridinic N atoms doped graphene surface (NG). β form of d‐glucose in alkaline solution was used… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(1 citation statement)
references
References 79 publications
0
1
0
Order By: Relevance
“…Therefore, searching for e cient electrocatalysts for C 6 H 12 O 6 oxidation is urgent and, also, an important challenge. Encouragingly, recent investigations have found that unsupported and supported Au-based catalysts are excellent candidates with no obvious poisoning [17][18][19][20][21]. Indeed, Cheng illustrated that the Au(111) surface capped with chiral phenylalanine shows good C 6 H 12 O 6 oxidation reactivity by DFT calculations [17].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, searching for e cient electrocatalysts for C 6 H 12 O 6 oxidation is urgent and, also, an important challenge. Encouragingly, recent investigations have found that unsupported and supported Au-based catalysts are excellent candidates with no obvious poisoning [17][18][19][20][21]. Indeed, Cheng illustrated that the Au(111) surface capped with chiral phenylalanine shows good C 6 H 12 O 6 oxidation reactivity by DFT calculations [17].…”
Section: Introductionmentioning
confidence: 99%